Potensi Pengembangan Sistem Integrasi Sapi dan Kelapa Sawit di Kelurahan Sungaiselan: Studi Kasus Kelompok Tani Tunas Baru Kelurahan Sungaiselan - Wika Wika; Fournita Agustina; Eddy Jajang Jaya Atmaja (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2019)
The cattle and oil palm integration program (SISKA) is a flagship program of the Provincial Government of Bangka Belitung Islands, especially in the Sungaiselan Village which synergizes cattle and oil palm in mutual relations. The objectives of this study are 1) to analyze the potential for SISKA development in Tunas Baru Farmers Group in Sungaiselan Village and 2) to analyze internal and external factors that are strengths, weaknesses, opportunities and safeguards in the SISKA strategy in Sungaiselan Village. This research method used a case study method which was analysed qualitatively. The analytical tool used wass SWOT. The results of this study indicated that 1) the potential development of SISKA in Sungaiselan was very large as seen from the potential of the Sungaiselan Village area, and the income received by farmers. 2) Internal factors in this study (strength): contribution of oil palm biomass as a source of feed, easy marketing, abundant SISKA by-products, maximum technology, and maximum ADG development; (weakness): HR capabilities were managed technically less, capital was limited, transportation systems were difficult and the difficulty was finding superior seeds. External factors in this study (opportunity): potential domestic meat prices, beef biomass as alternative energy, limited beef supply, increased beef demand, government policies in accelerating the development of SISKA (threats); imported meat prices were cheaper, the risk of animal mortality, and competitive competition.